2021
DOI: 10.1017/s1041610221000910
|View full text |Cite
|
Sign up to set email alerts
|

Activity engagement and psychological distress among Holocaust survivors during the COVID-19 pandemic

Abstract: Objectives: The COVID-19 pandemic may pose a specific threat for Holocaust survivors, as such threats may be linked with increased psychological distress. Moreover, research has demonstrated that engaging in planful problem-solving activities is associated with reduced distress. Accordingly, we aimed to examine the link between engaging in activities during COVID-19 and psychological distress among Holocaust survivors with varying levels of post-traumatic symptoms (PTS) and comparisons (not directly expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In other words, despite their relative vulnerability due to past trauma, a lower level of education and self-perceived health, the HS in our study demonstrated similar resilience to that of other older adults while coping with the unexpected threatening and long-lasting event of the COVID-19 pandemic. Although assessed differently, the coexistence of both vulnerability and resilience has been reported in previous studies conducted in Israel (e.g., [18,27]), probably because the HS that are still alive have developed specific psycho-behavioral coping patterns such as daily planning and activity engagement which was reported to reduce psychological distress during the Coronavirus pandemic even among HS with high PTSD levels [37], and may explain to some degree the ability of HS to reach old age in spite of their traumatic pasts.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In other words, despite their relative vulnerability due to past trauma, a lower level of education and self-perceived health, the HS in our study demonstrated similar resilience to that of other older adults while coping with the unexpected threatening and long-lasting event of the COVID-19 pandemic. Although assessed differently, the coexistence of both vulnerability and resilience has been reported in previous studies conducted in Israel (e.g., [18,27]), probably because the HS that are still alive have developed specific psycho-behavioral coping patterns such as daily planning and activity engagement which was reported to reduce psychological distress during the Coronavirus pandemic even among HS with high PTSD levels [37], and may explain to some degree the ability of HS to reach old age in spite of their traumatic pasts.…”
Section: Discussionmentioning
confidence: 87%
“…This may require developing additional professional practices and outreaching interventions directed to appropriately locating and addressing mental, physical and social needs. For instance, interventions to strengthen daily planning and activity engagement have been reported to reduce psychological distress during the Corona pandemic even among HS with high PTSD levels [37]. Additionally, intervention programs should include practices for maintaining and strengthening existing psychosocial protective resources such as the will to live.…”
Section: Discussionmentioning
confidence: 99%